Sandwich-Type Composites Based on Smart Ionomeric Polymer and Electrospun Microfibers - Sessini, Valentina; López Galisteo, Antonio Julio; Leonés, Adrián; Ureña, Alejandro; Peponi, Laura (Frontiers in Materials, 2019)
Take advance of the fiber-reinforced polymer process, commonly used in the fabrication of polymer composites, in this work we used electrospun microfibers to reinforce self-healing ionomeric polymers creating a sandwich-type composites. In particular, three-layer stack with poly(lactic acid), PLA, electrospun fibers in between two layers of commercial smart polymers has been obtained based on poly(ethylene-co-methacrylic acid ) (EMAA) copolymers, well-know with the tradename of Nucrel® and Surlyn®, both of them manufactured by Dupont™ Company. Surlyn® is the corresponding ionomer of Nucrel® in which the MAA groups are partially neutralized with sodium ions. In general, one of the main problem of thermoplastic composites is the high viscosity of the molten matrix, which leads to a difficult impregnation of the fiber bundle. Therefore, in this work, we used electrospun microfibers in order to solve impregnation problem, thus considering that electrospinning process is a simple, flexible and low-cost technique for fibers formation in the range of micron and nanometers. In order to create the sandwich-type structure, firstly, the optimization of the processing window has achieved in order to maintain the randomly oriented fiber structure on the final composites. In particular, the creation of sandwich-type structure with Surlyn® reinforced with woven non-woven electrospun fibers based on PLA with enhanced mechanical as well as hardness and wear resistance can be used for future active packaging solutions.